ANSWER
1.39
Step-by-step explanation
The given quadratic equation is
![0 = 2 {x}^(2) + 3x - 8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/h3rt2eh1ccghfen5ugp3pfzexjjigvc47z.png)
This is the same as,
![2 {x}^(2) + 3x - 8 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/onu21zuqv7wc8p0n54g2rrslxgu4neh8wd.png)
Comparing to
![a {x}^(2) + bx + c = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3i4p36yae7mlnttp9sryr8nhjit0psdlyi.png)
We have
a=2, b=3,c=-8
Using the quadratic formula, the solution is given by:
![x = \frac{ - b \pm \: \sqrt{ {b}^(2) - 4ac} }{2a}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hmipikl9td4tnhay6i1bv8h2ozrorfn68m.png)
We substitute the values to get,
![x = \frac{ - 3\pm \: \sqrt{ {3}^(2) - 4(2)( - 8)} }{2(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1vb7zjbju42wbqpkdq3y03n86x6c4sbo73.png)
![x = ( - 3\pm \: √( 73) )/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2xbddk41pld0gkf8o8gqtj4hefi04zfsu8.png)
The positive root is
![x = ( - 3 + \: √( 73) )/(4) = 1.39](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s3wt3rubd7sd4xtelb1rwwg6qvkmicaype.png)
to the nearest hundredth.